2014
DOI: 10.5194/se-5-121-2014
|View full text |Cite
|
Sign up to set email alerts
|

New insights on the occurrence of peperites and sedimentary deposits within the silicic volcanic sequences of the Paraná Magmatic Province, Brazil

Abstract: Abstract. The PMP (Paraná Magmatic Province) is characterized by lava flows of the Early Cretaceous Serra Geral Formation which covers about 75 % of the Paraná Basin (southern and southeastern Brazil), composed of a thick (up to 1600 m) volcanic sequence formed by a succession of petrographically and geochemically distinct units of basic and silicic composition. The whole package must have been emplaced during approximately 3 million years of nearly uninterrupted activity. A few aeolian sandstone layers, indic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 33 publications
0
8
0
1
Order By: Relevance
“…Peperites are frequently found at the base and interlayered within the silicic volcanic sequence (Luchetti et al, 2014), indicating periods of subaerial sedimentation before and between the silicic volcanic eruptions.…”
Section: Stratigraphymentioning
confidence: 99%
“…Peperites are frequently found at the base and interlayered within the silicic volcanic sequence (Luchetti et al, 2014), indicating periods of subaerial sedimentation before and between the silicic volcanic eruptions.…”
Section: Stratigraphymentioning
confidence: 99%
“…In the NW-PCFB, the basic lava interaction with wet, fine-grained sandstone resulted in fluidal peperites, whereas those containing irregular juvenile clasts are found in the central PCFB (Waichel et al, 2007(Waichel et al, , 2008. In addition, the jigsaw-fit texture peperites associated with rhyolites are reported for the southern PCFB by Luchetti et al (2014). The fluidal peperites associated with pahoehoe lavas of the NW-PCFB seem to be very similar to those of Hawaii.…”
Section: Lava Flow Morphology and Lava-sediment Interaction Relationsmentioning
confidence: 72%
“…Therefore, it is most likely that the effusive materials have such low viscosities (10 1 -10 3 Pa s; McBirney and Murase, 1984) and eruption temperatures ranging near liquidus (∼ 1150 • C; Helz and Thornber, 1987;Cashman et al, 1999). Instead, the rhyolite lavas that generated the peperites reported by Luchetti et al (2014) have the same characteristics as those found in Passamaquoddy Bay (Dadd and Van Wagoner, 2002), with low temperatures (∼ 800 • C) and high viscosity (10 8 -10 10 Pa s).…”
Section: Lava Flow Morphology and Lava-sediment Interaction Relationsmentioning
confidence: 75%
See 1 more Smart Citation
“…Dimitriadis, 2013; Luchetti et al, 2014). However, the occurrence of sediment-infill volcanic breccias in association with the Daginkatte rhyolites in the Neoarchean Shimoga belt is not in compliance with the above process for their generation and suggests an active continental margin setting marked by explosive volcanism and subsequent sedimentation.…”
Section: Sediment-infill Volcanic Breccia Of Shimoga Belt and Its Relmentioning
confidence: 87%